A Model of the Universe in Kathmandu's Old Royal Palace - Bühnemann, Gudrun (History of Science in South Asia, 2020)
This paper discusses a model of the universe found in Mohan courtyard of the old royal palace of Kathmandu, the Hanūmānḍhokā. It was commissioned and installed by King Pratāpa Malla in 1656 CE. The artifact is referred to as “earth-ball” or terrestrial globe (bhūgola) in an inscription and is based on Purāṇic concepts of the universe. An eighteenth-century ritual text indicates that it was an object of worship in the courtyard.